(untitled) (SCIENCE TIME JOURNAL, 2026)
Foreign Language Anxiety (FLA) is a pervasive emotional factor that significantly affects learners’ success in second language acquisition. This study explores the impact of FLA on university students’ academic performance in Uzbekistan, taking into account the cultural and institutional factors that shape students’ experiences. Employing a mixed-methods approach, data were collected using the Foreign Language Classroom Anxiety Scale (FLCAS) and students’ academic records, complemented by semi-structured interviews with participants exhibiting high anxiety levels.